Faktor-Faktor Yang Mempengaruhi Struktur Modal Perusahaan Pakaian Jadi Dan Tekstil. Apakah Ini Sektor Yang Berbeda? - Rizky, Rizky Ridwan; Dewi Ratnasari Astuti; Sri Julianti (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2024)
The aim of this research is to determine the effect of company size and asset growth on the capital structure of textile and garment companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach. The data collection technique used in sampling is non-probability sampling, namely a sample determination technique using certain considerations using financial reports from 2018-2022, some data needs to be outliers so that a final total of 48 companies in the research sample is obtained. The data analysis method used is multiple linear regression analysis using the SPSS 25 and Microsoft Excel 2010 programs. The results of the research state that simultaneously company size and asset growth have a significant effect on the capital structure of textile and garment companies listed on the Indonesia Stock Exchange.